New sesquiterpene coumarin from the roots of Ferula latisecta - Mehrdad Iranshahi; Farjad Amanolahi; Bernd Schneider (Mashhad University of Medical Sciences, 2012)
Objective: The genus of Ferula belongs to the tribe Peucedaneae, subfamily of Apioideae and family of Umbelliferae with 133 species distributed throughout the Mediterranean area and central Asia, especially in the former USSR and neighboring countries such as Iran. The popular Persian name of the most of these species is "Koma". In this research we tried to isolate and elucidate the structure of new sesquiterpene in the root of Ferula latisecta (F. latisecta). Materials and Methods: Dried and powdered roots of F. latisecta were extracted with CH2Cl2 using a Soxhlet apparatus. The extract was concentrated in vacuo to give a red extract. The extract was subjected to column chromatography on silica gel. 1H NMR, 13C NMR, DEPT, 1H-1H COSY, HMBC, HSQC, and NOESY spectra were the methods we used to elucidate the structure of new sesquiterpene in this plant. Results: One new sesquieterpene coumarin, namely Latisectin and IUPAC name [1-(2-Hydroxy-4-methoxy-phenyl)-3,4,8,12-tetramethyl-trideca-4,7,11-trien-1-one ] , together with one known compound , Kopetdaghin C, were isolated from the root of  F. latisecta. Conclusion: In this research the structure of one new and one known sesquiterpene in the root of F. latisecta was elucidated.